The ECSIM Concept (Environmental Control System for Intestinal Microbiota) and Its Derivative Versions to Help Better Understand Human Gut Biology - Brugère, Jean-François; Féria-Gervasio, David; Popse, Zsolt; Tottey, William; Alric, Monique (IntechOpen, 2011)
None